Cross-sectional study of the provision of interventional oncology services in the UK. Issue 10 (22nd October 2017) - Zhong, Jim; Atiiga, Peter; Alcorn, Des J; Kay, David; Illing, Rowland; Breen, David J; Railton, Nicholas; McCafferty, Ian J; Haslam, Philip J; Wah, Tze Min
Abstract : Objective: To map out the current provision of interventional oncology (IO) services in the UK. Design: Cross-sectional multicentre study. Setting: All National Health Service (NHS) trusts in England and Scottish, Welsh and Northern Ireland health boards. Participants: Interventional radiology (IR) departments in all NHS trusts/health boards in the UK. Results: A total of 179 NHS trusts/health boards were contacted. We received a 100% response rate. Only 19 (11%) institutions had an IO lead. 144 trusts (80%) provided IO services or had a formal pathway of referral in place for patients to a recipient trust. 21 trusts (12%) had plans to provide an IO service or formal referral pathway in the next 12 months only. 14 trusts (8%) did not have a pathway of referral and no plans to implement one. 70 trusts (39%) offered supportive and disease-modifying procedures. One trust had a formal referral pathway for supportive procedures. 73 trusts (41%) provided only supportive procedures (diagnostic or therapeutic). Of these, 43 (59%) had a referral pathway for disease-modifying IO procedures, either from a regional cancer network or through IR networks and 30 trusts (41%) did not have a referral pathway for disease-modifying procedures. Conclusion: The provision of IO services in the UK is promising; however, collaborative networks are necessary to ensure disease-modifying IO procedures are made accessible to all patients and to facilitate larger registry data for research with commissioning of new services.